Implementasi Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal : Studi Penyelenggaraan Jaminan Produk Halal di Provinsi Banten - Nadia Fatima; Ipah Ema Jumiati; Rina Yulianti (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2023)
The policies regarding Halal product guarantees are regulated in Law Number 33 of 2014. This Law aims to provide legal certainty regarding the halalness of a product circulating in public. In addition, it also created a sense of security and a sense of public trust in the products. Banten, which is well-known as one of the religious provinces, is also a benchmark for how the public has sufficient awareness and knowledge of the implementation of Halal Product Assurance (JPH) for products circulating in the market. This research is aimed to find out and analyze how the Implementation of Law Number 33 of 2014 concerning Guarantees for Halal Products (Studies on Implementation of Guarantees for Halal Products in Banten). The qualitative method was used in collecting data. The results of the research using the Edward III policy implementation model approach show that the implementation of Law Number 33 of 2014 concerning Halal Product Assurance (Study on the Implementation of Halal Product Guarantees in Banten) is still not going well. First, there is still confusion from businessmen in the flow of the halal certification registration process which is currently undergoing a transition period from LPPOM MUI to BPJPH. Second, there is no BPJPH organizational structure in the regions so it is currently under the Ministry of Religion in each province. Third, the regular Halal certification fee is quite expensive and affects the number of applicants for Halal certification. Forth, most Muslim communities do not know that Halal food products are not only strictly consuming pork and its derivatives. But it must be seen from the production process from upstream to downstream. Keywords: Public Policy Implementation, Law on Guarantees of Halal Products, Halal Certification.